Harmonizing Social Impact and Corporate Success: The Nexus of GOTO's Contribution to Society and Profitability - Dian Alanudin; Muhammad Miqdad Robbani (CV. Publikasi Indonesia, 2024)
This research examines the relationship between social impact and corporate profitability in the context of GoTo, Indonesia's largest technology conglomerate. This study analyzes GoTo's transformation from a simple ojek service to a comprehensive digital ecosystem, as well as its role during the COVID-19 pandemic. Using quantitative and qualitative mixed methods, this study investigates changes in consumer behavior, GoTo's economic contributions, and post-IPO challenges. Key findings show a significant increase in GoTo's service usage during the pandemic, with annual contributions reaching 1.6% of Indonesia's GDP. However, GoTo's pursuit of profitability post-IPO faces market volatility and regulatory scrutiny, particularly regarding driver-partner welfare. This research highlights the complexity of balancing social missions with the demands of profitability in the gig economy, emphasizing the importance of a holistic approach to sustainable growth that considers the interests of all stakeholders.